Antimicrobial susceptibilities in dairy herds that differ in dry cow therapy usage - McDougall S; Penry J; Dymock D (Elsevier Inc and the Federation of Animal Science Societies (Fass) Inc on behalf of the American Dairy Science Association, 2021)
Intramammary infusion of antimicrobials at the end of lactation (dry cow therapy; DCT) is a central part of mastitis control programs and is one of the major indications for antimicrobial use in dairy cows. However, with increasing focus on prudent use of antimicrobials and concerns about emergence of antimicrobial resistance, the practice of treating every cow at the end of lactation with DCT is in question. This cross-sectional, observational study determined the minimum inhibitory concentrations (MIC) of 10 antimicrobials for coagulase-negative staphylococci (CNS), Staphylococcus aureus, Streptococcus dysgalactiae, and Streptococcus uberis isolates from milk samples from dairy cows with somatic cell counts >200,000 cells/mL in herds that had been organic for >3 yr (n = 7), or had used either ampicillin-cloxacillin DCT (n = 11) or cephalonium DCT (n = 8) in the preceding 3 yr. The organic herds were certified under the United States Department of Agriculture National Organic Program, meaning that there was no blanket DCT, and minimal use of antimicrobials in general, with a loss of organic status of the animal if treated with antimicrobials. Breakpoints (where available) were used to categorize isolates as resistant, intermediate, or susceptible to antimicrobials. The MIC distributions of isolates from different herd types were compared using binomial or multinomial logistic regression. Of 240 CNS isolates, 12.9, 0.8, 7.1, 32.6, and 1.2%, were intermediate or resistant to ampicillin, cephalothin, erythromycin, penicillin, and tetracycline, respectively. Of 320 Staph. aureus isolates, 29.0, 2.5, 1.2, and 34.9% were intermediately resistant or resistant to ampicillin, penicillin, erythromycin, and oxacillin, respectively. Of 184 Strep. uberis isolates, 1.1, 25.0, 1.6, and 1.6% were intermediately resistant or resistant to erythromycin, penicillin, pirlimycin, and tetracycline, respectively. Generally, the MIC of CNS and streptococcal isolates from organic herds were lower than isolates from herds using DCT. However, the differences in MIC distributions occurred at MIC below clinical breakpoints, so that the bacteriological cure rates may not differ between isolates of differing MIC. Bimodal distributions of MIC for ampicillin and penicillin were found in Staph. aureus isolates from organic herds, suggesting that isolates with a higher MIC are a natural part of the bacterial population of the bovine mammary gland, or that isolates with higher MIC have persisted within these organic herds from a time when antimicrobials had been used. Given these observations, further work is required to determine if exposure to DCT is causally associated with the risk of elevated MIC, and whether reduction or removal of DCT from herds would reduce the risk of elevated MIC of mastitis pathogens.
Keywords: antimicrobial resistance; dairy cow; dry cow therapy; mastitis; Animals; Anti-Bacterial Agents; Anti-Infective Agents; Cattle; Cattle Diseases; Cross-Sectional Studies; Female; Mastitis, Bovine; Milk; Streptococcus